What kind of firm do you owner-manage? An institutional logics perspective of individuals' reasons for becoming an entrepreneur. Issue 3 (2nd September 2019) - Basco, Rodrigo
Abstract : Purpose: The purpose of this paper is to compare the post-entry firm behavior of firms owner-managed by entrepreneurs who entered for family-oriented vs opportunity-oriented reasons. Design/methodology/approach: Using the institutional logics perspective, the author argues that firms under the influence of opportunity-oriented or family-oriented owner-managers may differ in their internal practices, purpose, strategies, and performance. The author follows an inductive research methodology strategy by performing multivariate analyses with a sample of 1, 733 Chilean firms to explore the preliminary conjectures. Findings: Firms owner-managed by entrepreneurs who entered for a family-oriented reason finance their investment with firm resources, are less dependent on one customer and are willing to put forth less innovation effort than firms owner-managed by entrepreneurs who entered for an opportunity-oriented reason. No differences were found in terms of employee productivity. Additionally, the results show that young firms owner-managed by opportunity-oriented entrepreneurs have higher growth ratios than young firms owner-managed by family-oriented entrepreneurs. Inversely, old firms owner-managed by entrepreneurs who entered for an opportunity-oriented reason grow much less than old firms owner-managed by entrepreneurs who entered for a family-oriented reason. Originality/value: This paper contributes to the literature at the intersection of family business and entrepreneurship by addressing the calls made byAldrich and Cliff (2003) andDiscua Cruz and Basco (2018 ) to better understand the family's influence on entrepreneurship.